Secrets of a covalent interaction for biomaterials and biotechnology: SpyTag and SpyCatcher - Reddington, Samuel C; Howarth, Mark (Current opinion in chemical biology, 2015)
•SpyTag and SpyCatcher are peptide–protein partners that lock together covalently.•Reaction occurs in a wide range of protein contexts, buffers and temperatures.•One-to-one linkage enabled dramatic enzyme resilience and rapid vaccine generation.•Network linkage created tools for stem cell culture and living biomaterials. SpyTag is a short peptide that forms an isopeptide bond upon encountering its protein partner SpyCatcher. This covalent peptide interaction is a simple and powerful tool for bioconjugation and extending what protein architectures are accessible. Here we review the origin and mechanism of SpyTag/SpyCatcher, focusing on recent innovative applications. Ligation of targeting-antibody with antigen provided a simple route to vaccine generation. SpyRings, from head-to-tail cyclisation, gave major enhancements in enzyme resilience. Linking multiple SpyCatchers gave dendrimers for T-cell activation or Spy networks forming hydrogels for stem cell culture. Synthetic biology applications include integrating amyloid biomaterials with living bacteria, for irreversible derivatisation of biofilms with enzymes or nanoparticles. We also discuss further opportunities to apply and enhance SpyTag/SpyCatcher technology.